The Determination of Patient Learning Needs After Day Surgery: A Cross-Sectional Study - Üstündağ, Hülya; GÜL, ASİYE; Özkaya, Birgül (Elsevier, 2022)
Purpose: This study was conducted to investigate the care perception and learning needs of patients undergoing day surgery. Design: A descriptive and cross-sectional model was used. Methods: The study was conducted with 234 patients who underwent day surgery in a general surgery clinic of a university hospital. Data were collected using a sociodemographic characteristics form, the Patient Perception of Hospital Experience with Nursing Scale (PPHEN) and the Patient Learning Needs Scale (PLNS). Findings: The PPHEN mean score was 67.99 ± 11.98 and the PLNS total score was 211.15 ± 38.49. The subscales showed that the highest scores were 38.47 ± 6.93 for activities of life, while the lowest score was 20.60 ± 4.23 for feelings related to condition. There was a statistically significant negative correlation in the PPHEN and PLNS subscales in terms of medications, activities of living, treatment, and complications. There was no statistically significant relationship between the demographic data of the patients (age, gender, and educational status). Conclusions: This study demonstrated that patients had high information needs and greater concerns, particularly about "activities of life." Nurses should be aware of the importance of identifying high learning needs to increase the level of satisfaction with nursing care in day surgery patients.
Keywords: Ambulatory Surgery; Day Surgery; Learning; Perception